Fixed Point for Asymptotically Non-Expansive Mappings in 2-Banach Space - Abed, Salwa S.; Ali, Rafah S. Abed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In  this  paper, we  introduced   some  fact  in   2-Banach  space. Also, we define  asymptotically  non-expansive  mappings  in  the  setting  of  2-normed  spaces analogous  to  asymptotically non-expansive mappings  in  usual  normed spaces. And then prove the existence of fixed points for this type of mappings in 2-Banach spaces.